THE MOTIVATIONAL MODEL OF YOUNG JAPANESE EFL LEARNERS: AFTER GETTING LESSONS BY HOMEROOM TEACHERS - Adachi, Rie (Indonesian Journal of Applied Linguistics, 2013)
Abstract: This study focuses on Japanese pupilsâ€™ motivation with other attitudinal attitudes about learning English. The writer surveyed the 5th and 6th grade pupilsâ€™ motivation and its effect factors at an elementary school in Japan at the end of the school year 2007 and 2008. The main focus of this study is to find the relationship between motivation and effect factors using both the 2007 and 2008 data and to examine differences of the pupilsâ€™ attitudes between 2007 and 2008. Since the 2008 school year, pupils have received lessons by not only an assistant language teacher (ALT) but also their home room teachers (HRTs). The finding showed that the 2008 and 2007 results were similar in most valuables, but the value of â€œMotivationâ€ increased in 2008 compared to the previous year. Furthermore, â€œpeople around the learnerâ€ influenced on motivation more positively. Finally, this study presented a model which could be suggested as one of the motivational models of Japanese pupils for English activities. The writer concluded that the involvement of HRTs brought about generally good effects on pupilsâ€™ attitudes in this elementary school at this point.